[LB.03.08] SERUM CHLORIDE AND ADVERSE CARDIOVASCULAR EVENTS IN THE ANGLO SCANDINAVIAN CARDIAC OUTCOMES TRIAL (ASCOT). (September 2017) - McCallum, L.; Welsh, P.; Sever, P.; Sattar, N.; Padmanabhan, S.
Abstract : Objective: Data suggests that lower serum chloride (Cl-) is associated with higher mortality and cardiovascular risk in populations with hypertension or heart failure. In this study, we tested the association between serum Cl- and cardiovascular outcomes in the Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) Blood Pressure-Lowering Arm. Design and method: The Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) randomized a subset of 6549 patients at risk with no history of coronary heart disease to either atenolol-based or amlodipine-based BP lowering treatment and followed-up for 5.5 years. Serum Cl- was measured at baseline in 319 participants who had a cardiovascular event and 1361 controls, matched for age and sex. The primary outcome was a composite of fatal and non-fatal myocardial infarction, stroke and heart failure. Subjects were grouped into four categories based on Serum Cl- levels (Cl-< = 95; 95.1–105; 105.1–115; >115.1 mmol/L). The characteristics of the study population across these groups were compared using 1-way ANOVA for continuous variables and X2 test for categorical variables. Kaplan-Meier (KM) and Cox Proportional Hazard models (Cox-PH), adjusted for age, sex, body mass index, systolic blood pressure, smoking, diabetes, cholesterol, serum Na+, use of diuretics and randomisation group, were used to explore the multivariate adjusted association between baseline serum Cl- and cardiovascular events. Results: Participants with Cl- <95 mmol/L had a greater proportion of females (24.1 vs 11.9%; p 0.02) than those with Cl- >115.1, were slightly older (67.8[7.7] vs 65.3[7.5] years; p 0.01), had lower sodium (139[5] vs 142[3] mmol/L; p <0.01), and were more likely to be taking a diuretic (66.3 vs 28.9%; p < 0.01). Serum Cl- <95 mmol/L was associated with an increased risk of a cardiovascular event (HR 4.09[95% CI 1.17–14.32; p 0.03] independent of serum Na+ (1.01[0.97–1.5]; p 0.80) or diuretic use (1.13[0.89–1.42]; p 0.31) compared to those with serum Cl->115.1 mmol/L (figure). Conclusions: In the ASCOT study, serum chloride less than 95 mmol/L was associated with greater risk of cardiovascular events, independent of serum sodium or diuretic use. Figure. No caption available.